Effect of expansion media and fibronectin coating on growth and chondrogenic differentiation of human bone marrow-derived mesenchymal stromal cells - Valentina Basoli (Nature Portfolio, 2021)
Abstract In the field of regenerative medicine, considerable advances have been made from the technological and biological point of view. However, there are still large gaps to be filled regarding translation and application of mesenchymal stromal cell (MSC)-based therapies into clinical practice. Indeed, variables such as cell type, unpredictable donor variation, and expansion/differentiation methods lead to inconsistencies. Most protocols use bovine serum (FBS) derivatives during MSC expansion. However, the xenogeneic risks associated with FBS limits the use of MSC-based products in clinical practice. Herein we compare a chemically defined, xenogeneic-free commercial growth medium with a conventional medium containing 10% FBS and 5 ng/ml FGF2. Furthermore, the effect of a fibronectin-coated growth surface was investigated. The effect of the different culture conditions on chondrogenic commitment was assessed by analyzing matrix deposition and gene expression of common chondrogenic markers. Chondrogenic differentiation potential was similar between the FBS-containing αMEM and the chemically defined medium with fibronectin coating. On the contrary, the use of fibronectin coating with FBS-containing medium appeared to reduce the differentiation potential of MSCs. Moreover, cells that were poorly responsive to in vitro chondrogenic stimuli were shown to improve their differentiation potential after expansion in a TGF-β1 containing medium. In conclusion, the use of a xenogeneic-free medium provides a suitable alternative for human bone marrow MSC expansion, due the capability to maintain cell characteristic and potency. To further improve chondrogenic potential of BMSCs, priming the cells with TGF-β1 during expansion is a promising strategy.